Effects of urea associated with nitrapyrin on soil N-NH+4/N-NO-3 ratio and on corn yield - Cruz, A.P.; Neptune, A.M.L. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
A field experiment was carried out on a red-yellow latossol (LVA), medium texture, in order to evaluate the effects of rates of nitrapyrin (N-Serve 24E) and urea on N-NH+4/N-No-3 ratio, on the contents of total nitrogen in the leaves and in the grain of corn and on yield. The rates of nitrapyrin were 1, 2 and 3 kg/ha and the rates of nitrogen were 40 and 80 kg/ha. The following conclusions were drawn: the association of urea with 3 kg/ha of nitrapyrin increased the N-NH+4/N-NO-3 ratio of the soil and corn yield, but there was no variation in the total nitrogen contents in the leaf and in the grain.